The interplay of shape and catalyst distribution in the yield of compressible flow microreactors - C Antunes, G.; Jimenez Sanchez, Marco Aurelio; Malgaretti, P.; Bachmann, Julien; Harting, Jens (Journal of Chemical Physics, 2024)
We develop a semi-analytical model for transport in structured catalytic microreactors, where both reactant and product are compressible fluids. Using lubrication and Fick-Jacobs approximations, we reduce the three-dimensional governing equations to an effective one-dimensional set of equations. Our model captures the effect of compressibility, corrugations in the shape of the reactor, and an inhomogeneous catalytic coating of the reactor walls. We show that in the weakly compressible limit (e.g., liquid-phase reactors), the distribution of catalyst does not influence the reactor yield, which we verify experimentally. Beyond this limit, we show that introducing inhomogeneities in the catalytic coating and corrugations to the reactor walls can improve the yield.
CRIS-Team Scopus Importer:2024-10-04